2007
DOI: 10.1124/jpet.107.127027
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Characterization of a Human Carboxylesterase 2 Splice Variant

Abstract: (1-piperidino)-1-piperidino] carbonyloxycamptothecin or Irinotecan] is a carbamate prodrug that is activated in vivo by carboxylesterase (CES)-2 to SN-38 (7-ethyl-10-hydroxycamptothecin), a potent topoisomerase I inhibitor. There is high interindividual variation when CPT-11 is used in the treatment of colorectal cancer. Several splice variants of CES2 are reported in the expressed sequence tag database. Real-time polymerase chain reaction was used to determine the abundance of the CES2 and splice variant of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…For CES2, two isoforms (isoforms 1 and 2) are also available in the UniProtKB with isoform 1 being the canonical sequence. The sequence EASQAALQK is common to both CES2 isoforms; however, because the mRNA level of isoform 2 in the total CES2 transcript was very low (Schiel et al, 2007), the above sequence was assumed to be a specific fragment representing the function of CES2. CESs are known as glycoproteins (Kroetz et al, 1993) and therefore may complicate MS-based protein quantification because of posttranscriptional modifications such as glycosylation.…”
Section: Discussionmentioning
confidence: 99%
“…For CES2, two isoforms (isoforms 1 and 2) are also available in the UniProtKB with isoform 1 being the canonical sequence. The sequence EASQAALQK is common to both CES2 isoforms; however, because the mRNA level of isoform 2 in the total CES2 transcript was very low (Schiel et al, 2007), the above sequence was assumed to be a specific fragment representing the function of CES2. CESs are known as glycoproteins (Kroetz et al, 1993) and therefore may complicate MS-based protein quantification because of posttranscriptional modifications such as glycosylation.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that 5-FU significantly induces CES2 both in vitro and in vivo [ 8 ]. In particular, CES2 is highly expressed in colon tumors, playing a key role in the metabolic activation of CPT-11 [ 9 , 10 ]. Recent results have shown that the expression of CES2 is related to tumor staging [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…CPT‐11p, 7‐ethyl‐10‐[4‐(1‐piperidino)‐1‐piperidino] (carbonyloxycamptothecin or irinotecan), is a carbamate prodrug used to treat metastatic CRC, whose essential metabolic step is to activate CPT‐11 via carboxylesterase 1 (CES1), including CES1, CES2, and CES3 150 . Schiel et al 151 discovered the CES2Delta (458–473) protein, which lacks irinotecan hydrolase activity. Its transcripts were spliced at a relatively constant rate in tumor and normal colon tissues.…”
Section: The Role Of As In Crcmentioning
confidence: 99%